A Cost-Effective Reusable Tissue Mimicking Phantom for High Intensity Focused Ultrasonic Liver Surgery - Sitaramanjaneya Reddy Guntur; Seong-Chan Kim; Min-Joo Choi (Bioengineering, 2022)
A polyacrylamide polysaccharide hydrogel (PASG) containing a nonionic surfactant of the polyoxyethylene nonylphenyl ethers series (NP14) has been adapted to the fabrication of a reusable cost-effective ultrasonic tissue-mimicking phantom for real-time visualization of the thermal lesions by high intensity focused ultrasound (HIFU) irradiation. The constructed NP14 (40% in w/v) PASG is optically transparent at room temperatures, and it turns out to be opaque white as heated over the clouding points of about 55 °C and returns to its original transparent state after cooling. The acoustic property of the proposed phantom is similar to those of human liver tissues, which includes the acoustic impedance of 1.68 Mrayls, the speed of sound of 1595 ± 5 m/s, the attenuation coefficient of 0.52 ± 0.05 dB cm−1 (at 1 MHz), the backscatter coefficient of 0.21 ± 0.09 × 10−3 sr−1 cm−1 (at 1 MHz), and the nonlinear parameter B/A of 6.4 ± 0.2. The NP14-PASG was tested to assess the characteristic information (sizes, shapes, and locations) of the thermal lesions visualized when exposed to typical HIFU fields (1.1 MHz, focal pressure up to 20.1 MPa, focal intensity 4075 W/cm2). The proposed NP14-PASG is expected to replace the existing costly BSA-PASG used for more effective testing of the performance of therapeutic ultrasonic devices based on thermal mechanisms.